Féminisme Beauvoirien dalam Kumpulan Cerpen La Femme Rompue Karya Simone de Beauvoir - Nurlita Fitriah; Dewi, S.S., M.Hum., Evi Rosyani; Tri Widyastuti, Wahyu (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2024)
This research intends to gain the Beauvoirian feminism characteristics present in the collection of short stories La Femme Rompue by Simone de Beauvoir. These Beauvoirian feminism characteristics are as follows: 1. Women are capable of working; 2. Women can become intellectuals; 3. Women can work towards the social transformation of society; 4. Women can reject their otherness by identifying themselves through the perspectives of dominant groups in society. The research was conducted using a qualitative descriptive approach, with the primary data source being the short story collection La Femme Rompue by Simone de Beauvoir. The study utilizes a structural analysis method for literary works. Research data consists of words, phrases, and sentences from three short story titles within the collection La Femme Rompue. The analytical tool employed is a data analysis table based on Beauvoirian feminism theory. Prior to data analysis, the data is thoroughly read and understood. Subsequently, the data is presented in an analysis table categorized according to the relevant Beauvoirian feminism characteristics. The result of this study indicate that there are 36 quotations that reflect the Beauvoirian feminism characteristics in the collection of short stories La Femme Rompue. The Beauvoirian feminism characteristics that characteristics in the collection of short stories La Femme Rompue is women can reject their otherness by identifying themselves through the perspectives of dominant groups in society with a total of fifteen (15) quotes, followed by women can work towards the social transformation of society with a total of eight (8) quotes, then women can become intellectuals with a total of seven (7) quotes, while the least is women are capable of working with a total of six (6) quotes.